PENGARUH KUALITAS PELAYANAN DAN SUKU BUNGA TERHADAP LOYALITAS NASABAH DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI PADA UEK-SP AIR HITAM GEMILANG - Ardianto, Bagus; N, Arizal; Soviyanti, Efrita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study presents a new perspective in the study of financial services management, namely examining customer loyalty in community-based microfinance institutions through consumer behavior and relationship marketing approaches. This study not only replicates the model used in the banking sector, but also adapts it according to the socio-economic characteristics of UEK-SP Air Hitam Gemilang, so it is expected to be able to provide more contextual theoretical and empirical contributions in the development of microfinance services management literature at the village level. This study uses a quantitative approach. The quantitative approach is a research method that emphasizes theory testing through measuring research variables with numbers and data analysis using statistical procedures. The results of the study indicate that service quality has a positive and significant effect on customer loyalty in UEK-SP Air Hitam Gemilang. This is evidenced by the path coefficient value of 0.328 with a t-statistics value of 3.839 (> 1.96) and a p-value of 0.000 (< 0.05). Thus, H1 and H2, which state that service quality has a positive effect on customer loyalty, are accepted. The test results indicate that service quality has a positive and significant effect on customer trust at UEK-SP Air Hitam Gemilang. This is evidenced by a path coefficient of 0.459, a t-statistic of 9.321 (>1.96) and a p-value of 0.000 ( 1,96) dan p-value sebesar 0,000 (< 0,05). Dengan demikian, H1 dan H2 yang menyatakan bahwa kualitas pelayanan berpengaruh positif terhadap loyalitas nasabah dinyatakan diterima. Hasil pengujian menunjukkan bahwa kualitas pelayanan berpengaruh positif dan signifikan terhadap kepercayaan nasabah UEK-SP Air Hitam Gemilang. Hal ini dibuktikan oleh nilai koefisien jalur sebesar 0,459 dengan nilai t-statistics sebesar 9,321 (> 1,96) dan p-value sebesar 0,000 (< 0,05). Dengan demikian, hipotesis H4 dinyatakan diterima. Kata kunci: keuangan, UEK-SP, marketing, sektor perbankan